PHARMACY STUDENTS’ KNOWLEDGE, ATTITUDE, AND PRACTICE CONCERNING DIABETES AND ITS LONG-TERM COMPLICATIONS - A CROSS-SECTIONAL STUDY - SMRUTIMALLIKA DUTTA,; PRABHUDATTA MOHAPATRA,; KARMAJEET RATH,; DURGA MADHAB KAR, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The purpose of the study is to examine pharmacy students’ attitudes, knowledge, and behaviors related to diabetes mellitus, pinpoint any knowledge gaps, and evaluate their preparedness for patient education and effective treatment. Methods: Their knowledge, attitudes, and practices (KAPs) on diabetes and its long-term effects were evaluated by a cross-sectional, questionnaire-based study. A validated self-administered questionnaire was used to collect data, which was then analyzed using Statistical Package for the Social Sciences at a significance level of p<0.05. Results: The study involved 310 pharmacy students, including D. Pharm (n=48), B. Pharm (n=239), and M. Pharm (n=23) students. The survey found that the majority of pharmacy students had academic exposure to diabetes, with 91.29% having studied the topic. But there are still gaps in our understanding, especially when it comes to diabetic complications, dietary misunderstandings, and medication use (p<0.000). Attitudinal studies revealed considerable recognition of the pharmacist’s function but little support for counseling training. Students lacked practical experience, particularly in drug interaction monitoring, counseling, and adhering to rules. Conclusion: Pharmacy students demonstrated strong support for the pharmacist’s role in management, statistically significant results (p<0.05) in the majority of knowledge categories, and good knowledge and favorable attitudes toward diabetes care. However, major gaps in practical experience, such as patient counseling and guideline adherence, underscore the importance of hands-on training, workshops, and community engagement in improving clinical competence.